IGF2BP1 overexpression causes fetal-like hemoglobin expression patterns in cultured human adult erythroblasts - de Vasconcellos, Jaira F. (Proc Natl Acad Sci U S A, 2017)
Here we investigated in primary human erythroid tissues a downstream element of the heterochronic let-7 miRNA pathway, the insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1), for its potential to affect the hemoglobin profiles in human erythroblasts. Comparison of adult bone marrow to fetal liver lysates demonstrated developmental silencing in IGF2BP1. Erythroid-specific overexpression of IGF2BP1 caused a nearly complete and pancellular reversal of the adult pattern of hemoglobin expression toward a more fetal-like phenotype. The reprogramming of hemoglobin expression was achieved at the transcriptional level by increased gamma-globin combined with decreased beta-globin transcripts resulting in gamma-globin rising to 90% of total beta-like mRNA. Delta-globin mRNA was reduced to barely detectable levels. Alpha-globin levels were not significantly changed. Fetal hemoglobin achieved levels of 68.6 ± 3.9% in the IGF2BP1 overexpression samples compared with 5.0 ± 1.8% in donor matched transduction controls. In part, these changes were mediated by reduced protein expression of the transcription factor BCL11A. mRNA stability and polysome studies suggest IGF2BP1 mediates posttranscriptional loss of BCL11A. These results suggest a mechanism for chronoregulation of fetal and adult hemoglobin expression in humans.